Mode of gene action and heterosis for physiological, biochemical, and agronomic traits in some diverse rice genotypes under normal and drought conditions - Abd-El-Aty, Mohamed S.; Abo-Youssef, Mahmoud I.; Bahgt, Mohamed M.; Ibrahim, Omar M.; Faltakh, Hana; Nouri, Hela; Korany, Shereen Magdy; Alsherif, Emad A.; AbdElgawad, Hamada; El-Tahan, Amira M. (Frontiers in Plant Science, 2023)
Water scarcity is a crucial environmental stress that constrains rice growth and production. Thus, breeding for developing high-yielding and drought-tolerant rice genotypes is decisive in sustaining rice production and ensuring global food security, particularly under stress conditions. To this end, this study was conducted to evaluate the effects of water deficit on 31 genotypes of rice (seven lines, viz., Puebla, Hispagran, IET1444, WAB1573, Giza177, Sakha101, and Sakha105, and three testers, viz., Sakha106, Sakha107, and Sakha108) and their 21 crosses produced by line × tester mating design under normal and water deficit conditions; this was to estimate the combining ability, heterosis, and gene action for some traits of physiological, biochemical, and yield components. This study was performed during the summer seasons of 2017 and 2018. The results showed that water deficit significantly decreased relative water content, total chlorophyll content, grain yield, and several yield attributes. However, osmolyte (proline) content and antioxidant enzyme activities (CAT and APX) were significantly increased compared with the control condition. Significant mean squares were recorded for the genotypes and their partitions under control and stress conditions, except for total chlorophyll under normal irrigation. Significant differences were also detected among the lines, testers, and line × tester for all the studied traits under both irrigation conditions. The value of the σ²GCA variance was less than the value of the σ²SCA variance for all the studied traits. In addition, the dominance genetic variance (σ2D) was greater than the additive genetic variance (σ2A) in controlling the inheritance of all the studied traits under both irrigation conditions; this reveals that the non-additive gene effects played a significant role in the genetic expression of the studied traits. The two parental genotypes (Puebla and Hispagran) were identified as good combiners for most physiological and biochemical traits, earliness, shortness, grain yield, and 1,000-grains weight traits. Additionally, the cross combinations Puebla × Sakha107, Hispagran × Sakha108, and Giza177 × Sakha107 were the most promising. These results demonstrated the substantial and desirable specific combining ability effects on all the studied traits, which suggested that it could be considered for use in rice hybrid breeding programs.